2019
DOI: 10.3390/separations6040054
|View full text |Cite
|
Sign up to set email alerts
|

Recent Applications and Newly Developed Strategies of Solid-Phase Microextraction in Contaminant Analysis: Through the Environment to Humans

Abstract: The present review aims to describe the recent and most impactful applications in pollutant analysis using solid-phase microextraction (SPME) technology in environmental, food, and bio-clinical analysis. The covered papers were published in the last 5 years (2014–2019) thus providing the reader with information about the current state-of-the-art and the future potential directions of the research in pollutant monitoring using SPME. To this end, we revised the studies focused on the investigation of persistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 225 publications
0
11
0
Order By: Relevance
“…The concentrations of the aroma compounds were analyzed in the permeate, retentate, and feed streams by gas chromatography coupled with mass spectrometry (GC-MS), using headspace solidphase microextraction (HS-SPME) as a convenient and suitable sample preparation approach, which is widely used in several application fields [29][30][31][32]. SPME was performed using an 85 µm carboxen/polydimethylsiloxane fiber, which demonstrated to be a suitable coating for the assay of Three different spiral-wound membranes (SG1812C-34D, SE1812C-34D and SC1812), all supplied by GE Water & Process Technologies (Minnetonka, MN, USA), were tested.…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of the aroma compounds were analyzed in the permeate, retentate, and feed streams by gas chromatography coupled with mass spectrometry (GC-MS), using headspace solidphase microextraction (HS-SPME) as a convenient and suitable sample preparation approach, which is widely used in several application fields [29][30][31][32]. SPME was performed using an 85 µm carboxen/polydimethylsiloxane fiber, which demonstrated to be a suitable coating for the assay of Three different spiral-wound membranes (SG1812C-34D, SE1812C-34D and SC1812), all supplied by GE Water & Process Technologies (Minnetonka, MN, USA), were tested.…”
Section: Methodsmentioning
confidence: 99%
“…Although originally univariate (i.e., one factor at a time) optimization was used (step‐by‐step optimization), the later introduction of multivariate optimization designs helped for the quick SPME parameters optimization. There are range of options of SPME fibers commercially available, however, considerable efforts have been made by researchers to attempt coating with novel materials such as metal‐organic frameworks, nanocomposites, nanotubes, mesoporous materials, and polymer materials to improve the efficiency of SPME protocol [22,29,30]. Moreover, apart from the modification in fiber coatings, various types of SPME devices/extraction protocols are also developed including automation adoptability.…”
Section: Introductionmentioning
confidence: 99%
“…However, review articles comprising HBM of these environmental contaminants/emerging pollutants in various human specimens and studies on population‐wise exposure levels using SPME are scarce. There are several recent studies demonstrated the use of SPME method for the measurement of several ECs in various human specimens (urine, serum, blood, hair, saliva) and they were partially covered in a few recent review articles aimed at different scopes [29,41]. Hence, this review article mainly focuses on summarizing applicability of SPME for HBM (base‐line exposure levels, demographic based exposure patterns, risks assessment, case–control study, epidemiological cohort study) of various classes of ECs and future perspectives of SPME for emerging HBM/exposomic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, SPME has become a well-established sample-prep technique for simultaneous extraction and preconcentration of compounds from a variety of matrices [4][5][6][7]. Given the simplicity, versatility, and availability of different formats, SPME addresses several challenges associated with the traditional sample preparation approaches and allows for a substantial streamlining of the analytical workflow.…”
mentioning
confidence: 99%
“…Over the decades, its remarkable evolution has led to new in vivo applications [8][9][10], development of methods for the analysis of complex matrices [4,[11][12][13][14], use of new coating materials [15][16][17][18][19], but also development of new devices and geometries [20,21]. Although it has been recently utilized in ambient mass spectrometry, its use in conjunction with the chromatographic approaches is now consolidated, while experimental design techniques are recommended for efficient multivariate optimization of the working variables which affect the SPME performance [3,[22][23][24].…”
mentioning
confidence: 99%